Occupational characteristics of seafarers in Miag-ao and their assessment of their working condition - Garcia, Stella Marie E.; Naquita, Loren Mae M. (2006.)
This study aims to find out the relationship between occupational characteristics of the seafarers in Miag-ao and their assessment of their working condition.
Keywords: Seafarers -- Miag-ao, iloilo